(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Rate of complications after conducted endodontic treatment remains high despite of constant introduction of the newest endodontic tools, materials, and technologies. Exacerbation of chronic apical periodontitis (CAP) is quite often accompanied by disturbance of general condition, pain syndrome, hyperemia, edema of mucous tunic of alveolar bone, and by collateral edema of soft tissues of face. During inflammatory processes the medium molecules are formed in tissues and biologic fluids, these molecules are considered to be non-specific markers of endogenous intoxication. Hirudotherapy (HT) is an example of the significant positive effect of a natural living organism on the person who suffers from pathologies of various systems. Secretion of medicinal leech (MP) contains such bioactive substances as hirudin, bdellines, hirustasin, destabilase, hyaluronidase, eglines, inhibitors of kallikrein of blood plasma, and unidentified compounds that provide analgesic, antioxidant, immunostimulant, bacteriostatic, lipolytic, and other properties. Materials and Methods: Clinical material from 82 patients was analyzed. They were divided into two groups: The main one and the comparison one. Conventional endodontic treatment was conducted in all cases. In case of exacerbation of CAP, the HT was used in the main group together with the conventional endodontic treatment in all patients; and pharmacotherapy was used in the comparison group. Results and Discussion: Conducted clinical and laboratory research showed clinical effectiveness of HT in patients with exacerbation of CAP.